Changes in double poling forces and cycle characteristics during cross-country skiing sprint competition - Mikkola, J.; Laaksonen, M. S.; Holmberg, H. C.; Linnamo, V. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: "Modern" double poling (DP), introduced by Holmberg et al. (2005), is the most used technique in the classical cross-country skiing sprint (XCSS) competitions. However, there is no published data about how pole forces change during XCSS using DP due to fatigue. The aim of this study was thus to investigate changes in pole forces and cycle characteristics during XCSS.